Penerapan Model Problem based learning (PBL) dalam Meningkatkan Pemahaman Keluargaku Unik di Kelas II (Penelitian di MI Al Munawwar) - Rizal Ibrahim Aji; Syamsurrijal; Luthfi Ahmad Fadilah (Universitas Muhammadiyah Kuningan, 2025)
The implementation of Problem-Based Learning (PBL) in second-grade elementary classrooms at MI Al Munawwar focuses on enhancing students' understanding of the topic Keluargaku Unik (My Unique Family). This learning approach aims to improve students' comprehension of descriptive texts, sentence construction, and self-expression through active and innovative participation. The research involved two classes, with one employing PBL and the other using traditional teaching methods. Conducted over two weeks, the study assessed students' understanding through pretests, posttests, and classroom observations. The results revealed that PBL significantly improved students' comprehension and engagement compared to traditional methods, with a noticeable increase in their ability to describe family uniqueness and construct coherent sentences. The students' positive responses and active participation demonstrate PBL's effectiveness in fostering critical thinking and meaningful learning experiences. This activity not only promotes academic achievement but also encourages collaborative and reflective learning, essential for holistic development.